KEPUTUSAN BERKUNJUNG PADA HOTEL IBIS DI SURAKARTA - Nurdiansyah Kristianto; Sudarwati Sudarwati; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2020)
The aim of this research are to find out the simultaneous and partial influence between partnership, facility and brand image toward visit decision at Ibis Hotel in Surakarta. The population in this study were ibis hotel customers in Surakarta in the October-November 2019 period, totaling 209 registered members. The samples in this study were 104 respondents. Data collection techniques in this research were using observation, documentation, and questionnaires. Technical data analysis in this research were using classic assumption test, multiple linier test, t test, f test, the coefficients determined. The result of this study: there is simultaneous influence between partnership, facility and brand image toward visit decision at Ibis Hotel in Surakarta. There is partial influence between partnership, facility and brand image toward visit decision at Ibis Hotel in Surakarta Key words: partnership, facility, brand image, visit decision